2018
DOI: 10.3168/jds.2018-14986
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Confirmation of candidate causative variants on milk composition and cheesemaking properties in Montbéliarde cows

Abstract: In a previous study, we identified candidate causative variants located in 24 functional candidate genes for milk protein and fatty acid composition in Montbéliarde, Normande, and Holstein cows. We designed these variants on the custom part of the EuroG10K BeadChip (Illumina Inc., San Diego, CA), which is routinely used for genomic selection analyses in French dairy cattle. To validate the effects of these candidate variants on milk composition and to estimate their effects on cheesemaking properties, a genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
14
0
1
Order By: Relevance
“…In addition to the three well-known QTL regions described above, we also found evidence that other genomic regions have highly significant effects on the traits analyzed; specifically, our analysis highlighted the SLC37A1 , ALPL , MGST1 , SEL1L3 , FASN , ANKH , BRI3BP , SCD , and GPAT4 genes, which we had also previously detected in a sequence-based GWAS on milk protein and fatty acid composition [45, 46]. We confirm here their effects on milk composition and note their effects on CMP.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to the three well-known QTL regions described above, we also found evidence that other genomic regions have highly significant effects on the traits analyzed; specifically, our analysis highlighted the SLC37A1 , ALPL , MGST1 , SEL1L3 , FASN , ANKH , BRI3BP , SCD , and GPAT4 genes, which we had also previously detected in a sequence-based GWAS on milk protein and fatty acid composition [45, 46]. We confirm here their effects on milk composition and note their effects on CMP.…”
Section: Discussionsupporting
confidence: 71%
“…The result was consistent with the previous studies. In Montbéliarde cows 17 , a similar two-step imputation strategy was used to impute preselected sequencing SNPs when using a customized low-density SNP chip as a reference panel. In other dairy cattle populations, a multiple-step imputation strategy was superior to a one-step imputation strategy when imputing from 3 K and 6 K chips to the HD chip where animals were firstly imputed to the 54 K chip and then to the HD chip 31 , or from the 54 K chip to WGS where animals were firstly imputed to the HD chip and then to WGS 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead of using the WGS data as a reference panel, using a customized low-density chip could achieve a much larger reference population but with lower linkage disequilibrium between preselected sequencing SNPs and the other SNPs in the chip. By using a customized low-density SNP chip as a reference panel, Sanchez et al 17 imputed 194 candidate variants for milk protein and fatty acid composition in Montbéliarde cows and showed that the mean squared correlation between imputed and true genotypes was 91.6% for SNPs with MAF higher than 1%.…”
mentioning
confidence: 99%
“…Grâce à l'imputation réalisée sur les vaches From'MIR (Sanchez et al, 2018b), nous avions à disposition les génotypes de la puce 50K augmentée des SNP de la partie recherche de la puce EuroG10K. Parmi les SNP de la partie recherche, figuraient certains variants candidats (prédictifs ou causaux) dont les effets sur la composition du lait ont été mis en évidence dans le projet PhénoFinlait (Boichard et al, 2014 ;Sanchez et al, 2017) et confirmés dans le projet From'MIR (Sanchez et al, 2018b). Dixhuit de ces variants (SNP), représentant chacun une région QTL avec de gros effets sur la composition et/ou la « fromageabilité » du lait, ont ainsi été sélectionnés.…”
Section: Précision D'une éValuation Génomiqueunclassified